Melamine exposure threshold in early chronic kidney disease patients – A benchmark dose approach. (November 2021) - Chen, Chu-Chih; Tsai, Yi-Chun; Wang, Yin-Han; Wu, Chia-Fang; Chiu, Yi-Wen; Hwang, Shang-Jyh; Liu, Chia-Chu; Hsieh, Tusty-Jiuan; Wu, Ming-Tsang
Highlights: The lower bound of benchmark dose (benchmark response 0.1) ranged from 0.74 to 2.03 μ g / k g _ b w / d a y . A threshold one to two orders lower than the WHO and US FDA recommended levels. Consistent associations with kidney outcomes over a median follow-up of 7.0 years. Early-stage CKD patients is more susceptible to melamine than urolithiasis patients. Abstract: Environmental melamine exposure has been associated with deteriorating kidney function in early-stage chronic kidney disease patients. In this study, a benchmark dose (BMD) approach was used to establish melamine exposure threshold in 293 patients with eGFR ≥ 30 ml/min per 1.73 m 2 . The patients were enrolled 2006–2010 and followed-up for a median of 7.0 years to monitor kidney outcomes. Average daily intakes (AvDI) of melamine were estimated using one-spot urine samples collected at enrollment. BMDs and corresponding one-sided 95% lower bound (BMDLs) were derived using established dose–response models relating estimated AvDIs and dichotomous kidney outcomes: doubling of serum creatine levels, eGFR decreased > 3 ml/min per 1.73 m 2 per year, and >30% decline in eGFR during the first 2 years. In addition, survival time to doubling of serum creatinine and eGFR decline over time were assessed as continuous endpoints. Given a benchmark response of 0.10, BMDLs ranged from 0.74 to 2.03 μ g / k g _ b w / d a y after Bayesian model averaging, a range one to two orders lower than the current WHO recommended tolerable daily intake of 200 μ g / k g _ b w / d a y and the US FDA's 63 μ g / k g _ b w / d a y . Our results suggest that early-stage CKD patients should strictly refrain from using melamine tableware and related melamine-made products.